A Context for Mozart's French Ariettes: The Wendling Family and Friedrich Schiller's Kabale und Liebe - Corneilson, Paul (Current Musicology, 2006)
This essay examines Mozart's relationship to the Wendling family and the French ariettes he wrote during his visit to Mannheim. Through documen-tary evidence we glimpse the underside of court life, involving an affair between Elisabeth Augusta Wendling and Elector Palatine Carl Theodor. Six years after Mozart's visit, Friedrich Schiller's Kabale und Liebe was performed at the Mannheim National Theater in 1784. The goal of the essay is first to draw connections between Mozart and the Wendlings, and second to consider Schiller's fictional Luisa Miller, her father, and mother-a family possibly modeled on the Wendlings.